(untitled) (Revista Contexto & Educação, 2025)
The beginnings of higher education in Latin America date back to the dawn of colonization, which was a significant milestone in the historical and social development of the continent. This process is framed within the context of European colonialist expansion, which was characterized by an embryonic and expansive phase of European dominions and burgeoning mercantilist capitalism. The objective of this article is to characterize processes that influence the constitution of the different Argentine university models, in order to systematize an analytical synthesis that allows understanding how these factors are articulated with theoretical conceptions of universities in the Latin American region. The qualitative approach of this study is influenced by the conception of historical-structural dependence of Latin American societies, based on theoretical-methodological assumptions of a Marxist perspective. Through a specification of the economic, political and social dimensions of each moment, it is shown how certain historical conditions influenced the constitution of the different Argentine university models. This, in turn, allowed for the development of an analytical synthesis to understand how these factors are presented in the ethical-political conceptions of universities in the Latin American region.